Rhesus alloimmunization in pregnancy. A Tertiary Care Center Experience in Kenya. A Case Report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Rhesus alloimmunization is a significant cause of perinatal morbidity in sub-SaharanAfrica.Case presentation: A 28-year-old para 2+2 gravida 5, rhesus-negative mother with no living childpresented to the Kenyatta National Hospital (KNH) antenatal clinic at 20 weeks of gestation as a referralbecause of a bad obstetric history secondary to rhesus D alloimmunization following a positive indirectCoombs test. She was started on methylprednisolone, and serial middle cerebral artery peak systolicvelocity (MCA-PSV) monitoring was performed until 32 weeks of gestation when the fetus developedhemolytic disease of the newborn diagnosed via cordocentesis. She underwent two sessions ofintrauterine transfusion and had a successful cesarean delivery at 34 weeks and 1 day of gestation. Theneonate was admitted to the KNH neonatal intensive care unit where he was managed for hemolyticdisease of the newborn, 33 days after which he was successfully discharged home.Conclusion: The role of maternal-fetal specialists in the diagnosis, antenatal follow-up, and timelymanagement of rhesus D alloimmunization is key in the prevention of adverse perinatal outcomes.